(untitled) (Cadernos de Sociomuseologia, 2009)
Abstract This work presents a characterization of the portuguese secondary schools concerning their (aptitude to) participation in museological activities. From a starting universe of 472 secondary schools and after telephonic contacts specifically improved, a final target population of 86 schools has been selected and then each one of them was visited. The processing and interpretation of a model inquest carried out in the course of those visits, allowed the delimitation of l6 school categories. The school(s) included in each category were then analysed in an attempt to identify and understand the major problems related to their particular realities and responsible for the difficult situation that school museums in Portugal nowadays have to face. Resumo O trabalho de investigação cujos resultados aqui se apresentam, foi realizado como objectivo de caracterizar as escolas secundarias portuguesas relativamente ao seu envolvimento, real ou potencial, em actividades do domínio da museologia. A populacao-alvo inicial era constituída por 472 escolas, das quais foram seleccionadas 86, após contactos telefónicos especificamente estruturados. Esta populacao-alvo final foi então objecto de visitas programadas, acompanhadas por entrevistas a que serviu de orientação um modelo de inquérito especificamente elaborado. O tratamento dos dados assim obtidos conduziu a distribuição dos 86 perfis analisados por 16 categorias. Procedeu-se então a análise comparativa das escolas incluídas em cada categoria, dando ênfase a identificação dos principais factores que condicionam, actualmente, o desenvolvimento da museologia em meio escolar em Portugal.